Diet – Related Risk Factors for Incident Hypertension in Malawili, Sorong, West Papua, Indonesia - Asmuruf, Mersy Marselina; Martini, Martini; Setyawan, Henry; Widjanarko, Bagoes; Musthofa, Syamsulhuda Budi (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Backgrounds:Hypertension sufferers in Aimas District in 2022 (31,3%) due to unhealthy lifestyle consumption behavior, namely liking or often eating stir-fried vegetables (water spinach, cassava leaves), fried fish or cooked in yellow sauce and sports or physical activity less than 150 minutes/week. in addition to supporting factors of a hereditary history of hypertension.Methods: The study used cross-sectional quantitative Observational and deskriptive analytic by non-random sample accidental sampling. In total, 200 populations (100 cases) were included in the study. Variable were fruit & vegetable diets, unhealthy fatty food, alcohol and cigarette consumption, and exercises. Data wereResult: Variables contribute to hypertensions were; Poor vegetable consumption behavior (53,0%) analysed Univariad, Consume vegetables (p= 0,019), Excessive fat consumption (p= 0,004), Exercise (p= 0,007), body mass index (p= 0,029); Genetic (p= 0,002); Cholestrol (p= 0,004); Stir-fry water spinach (p= 0,000); and . Hence, fruits, alcohol & cigarette consumptions were not correlated as contributing factors for incident hyperthension (p= 0,396; p-value=0,228; p-value=0,767).Conclusions: Risk factors for hypertension could be controlled and/or avoidable through healthy diet and lifestyle especially for those with unavoidable hereditary risk factorsKeywords : Behavior,Healthy,Consumption Hypertension